2019
DOI: 10.1093/infdis/jiz271
|View full text |Cite
|
Sign up to set email alerts
|

Once-Weekly Oral Dosing of MK-8591 Protects Male Rhesus Macaques From Intrarectal Challenge With SHIV109CP3

Abstract: Background MK-8591 (4′-ethynyl-2-fluoro-2′-deoxyadenosine [EFdA]) is a novel reverse transcriptase–translocation inhibitor. Methods We assessed MK-8591 as preexposure prophylaxis in the rhesus macaque model of intrarectal challenge with simian/human immunodeficiency virus (SHIV). In study 1, 8 rhesus macaques received 3.9 mg/kg of MK-8591 orally on day 0 and once weekly for the next 14 weeks. Eight controls were treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 29 publications
2
30
0
Order By: Relevance
“…7b) and demonstrated sustained MK-8591-TP concentrations far in excess of the in vitro 50% effective concentration (EC 50 ) (36). The PCL and EVA implants achieved intracellular MK-8591-TP concentration at the same order of magnitude that conferred complete protection in the rectal SHIV challenge study, 0.8 pmol/10 6 PBMCs (29). From the nonhuman primate study, we predicted the MK-8591 plasma PK in humans from the 50 wt% MK-8591 in PCL implants and compared to clinical PK of once-weekly oral doses of MK-8591.…”
Section: Discussionmentioning
confidence: 92%
“…7b) and demonstrated sustained MK-8591-TP concentrations far in excess of the in vitro 50% effective concentration (EC 50 ) (36). The PCL and EVA implants achieved intracellular MK-8591-TP concentration at the same order of magnitude that conferred complete protection in the rectal SHIV challenge study, 0.8 pmol/10 6 PBMCs (29). From the nonhuman primate study, we predicted the MK-8591 plasma PK in humans from the 50 wt% MK-8591 in PCL implants and compared to clinical PK of once-weekly oral doses of MK-8591.…”
Section: Discussionmentioning
confidence: 92%
“…Alternatively, another potent, long-acting small molecule ARV like cabotegravir (4648) or GS-6297 (49) could be progressed with studies like those shown in this work to achieve the goal of a long-acting subcutaneous implant for the treatment and prevention of HIV infection. 4’-ethynyl-2-fluoro-2’-deoxyadenosine (EFdA, Islatravir, MK-8591) (4648) is a highly potent nucleoside reverse transcriptase translocation inhibitor: once-weekly oral dosing has demonstrated its ability to protect male rhesus macaques in challenge studies(50). Implantable islatravir implants have demonstrated prophylactic concentrations in a human trial (51, 52).…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, another potent, long-acting, small-molecule ARV, like cabotegravir (39-41) or GS-6207 (42), could be progressed with studies like those shown in this work to achieve the goal of a long-acting subcutaneous implant for the treatment and prevention of HIV infection. 4=-Ethynyl-2-fluoro-2=-deoxyadenosine (EFdA) (islatravir; MK-8591) (39-41) is a highly potent nucleoside reverse transcriptase translocation inhibitor: once-weekly oral dosing has demonstrated its ability to protect male rhesus macaques in challenge studies (43). Islatravir implants have demonstrated prophylactic concentrations in a human trial (9,44).…”
Section: Discussionmentioning
confidence: 99%